2013
DOI: 10.1002/lt.23680
|View full text |Cite
|
Sign up to set email alerts
|

Comparable graft and patient survival in lean and obese liver transplant recipients

Abstract: Obesity is among the great health problems facing Americans today. More than 32% of the US population is considered obese on the basis of a body mass index (BMI) exceeding 30 kg/m 2 . Obesity increases the risk for numerous perioperative complications, but how obesity affects the outcome of liver transplantation remains unclear. We compared graft/patient survival after orthotopic liver transplantation performed at the Cleveland Clinic between April 2005 and June 2011 in 2 groups: obese patients with a BMI 38 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 37 publications
4
54
1
3
Order By: Relevance
“…This surgery may be performed before, after or even during the transplantation. 171 One significant concern is the potential impact of obesity on the outcomes from liver transplantation. Recently, it was observed that surgical mortality, two-year survival and graft viability were similar in obese and lean individuals.…”
Section: Bariatric Surgery In Cirrhotic Patientsmentioning
confidence: 99%
“…This surgery may be performed before, after or even during the transplantation. 171 One significant concern is the potential impact of obesity on the outcomes from liver transplantation. Recently, it was observed that surgical mortality, two-year survival and graft viability were similar in obese and lean individuals.…”
Section: Bariatric Surgery In Cirrhotic Patientsmentioning
confidence: 99%
“…Perioperative morbidity is slightly higher. 2,3 Performing bariatric surgery in non--compensated transplant candidates leads to higher morbidity and mortality, including the occurrence of anastomotic fistulas, which often reaches 12.5%. 21,22 Recently, there has been growing interest in the possibility of endoluminal treatments for obesity in individuals with high surgical risk.…”
Section: Resultsmentioning
confidence: 99%
“…1 Likewise, the prevalence of obesity among cirrhotic individuals who are candidates for liver transplantation has almost doubled since the 1990s, reaching more than 30%. 2,3 Furthermore, obesity and metabolic syndrome have presented an increasingly significant causal relationship with chronic liver disease. 4 Non-alcoholic fatty liver disease (NAFLD) is currently the third leading cause of liver transplantation in the United States of America (USA).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating United Network for Organ Sharing/Organ Procurement and Transplantation Network (UNOS/OPTN) and United Kingdom Transplant data similarly report worse outcomes in obese patients, notably due to increased graft dysfunction, frequency of cardiovascular events, infectious complications, and longer hospital stays [11,12] . However, conflicting data from Perez-Protto noted no significant differences in perioperative morbidity and mortality in lean (BMI 20-26 kg/m 2 ) versus obese (BMI>38 kg/m 2 ) liver transplant recipients [13] . Nevertheless, given the evidence regarding the negative impact of comorbid obesity, liver transplant providers routinely attempt to address this disease with standard of care approaches including dietary counseling, exercise programs, and behavioral therapies during transplant evaluation and waitlist management.…”
Section: Research Highlightmentioning
confidence: 97%